Focused Ultrasound Thalamotomy Sensory Side Effects Follow the Thalamic Structural Homunculus. Issue 4 (August 2021) - Paff, Michelle; Boutet, Alexandre; Germann, Jürgen; Elias, Gavin J.B.; Chow, Clement T.; Loh, Aaron; Kucharczyk, Walter; Fasano, Alfonso; Schwartz, Michael L.; Lozano, Andres M.
Abstract : Objective: Focused ultrasound thalamotomy is an effective treatment for tremor; however, side effects may occur. The purpose of the present study was to investigate the spatial relationship between thalamotomies and specific sensory side effects and their functional connectivity with somatosensory cortex and relationship to the medial lemniscus (ML). Methods: Sensory adverse effects were categorized into 4 groups based on the location of the disturbance: face/mouth/tongue numbness/paresthesia, hand-only paresthesia, hemibody/limb paresthesia, and dysgeusia. Then, areas of significant risk (ASRs) for each category were defined using voxel-wise mass univariate analysis and overlaid on corresponding odds ratio maps. The ASR associated with the maximum risk was used as a region of interest in a normative functional connectome to determine side effect–specific functional connectivity. Finally, each ASR was overlaid on the ML derived from normative template. Results: Of 103 patients, 17 developed sensory side effects after thalamotomy persisting 3 months after the procedures. Lesions producing sensory side effects extended posteriorly into the principle sensory nucleus of the thalamus or below the thalamus in the ML. The topography of sensory adverse effects followed the known somatotopy of the ML and the sensory nucleus. Functional connectivity patterns between each sensory-specific thalamic seed and the primary somatosensory areas supported the role of the middle insula in processing of gustatory information and in multisensory integration. Conclusions: Distinct regions in the sensory thalamus and its afferent connections rise to specific sensory disturbances. These findings demonstrate the relationship between the sensory thalamus, ML, and bilateral sensory cortical areas.